2005
DOI: 10.1038/sj.npp.1300914
|View full text |Cite
|
Sign up to set email alerts
|

The Serotonergic Hypothesis for Depression in Parkinson's Disease: an Experimental Approach

Abstract: The serotonergic hypothesis for depression in Parkinson's disease (PD) states that the reduced cerebral serotonergic activity that occurs in PD constitutes a biological risk factor for depression. The aim of our study was to assess the serotonergic hypothesis of depression in PD patients using an experimental approach. In a double-blind, randomized order, placebo-controlled crossover design, the response on the Profile of Mood States (POMS) questionnaire to acute tryptophan depletion (ATD) was studied in 15 PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 53 publications
4
25
3
Order By: Relevance
“…It should be mentioned though that evidence against the model has been found in an ATD study in Parkinson's disease (PD) patients. 383 This study found no support for SV in PD patients, although these patients generally have reduced 5-HT activity and an increased risk of depression. These results may debilitate the model, although there may be several possible explanations for the negative finding.…”
Section: Limitations Of the Modelcontrasting
confidence: 54%
“…It should be mentioned though that evidence against the model has been found in an ATD study in Parkinson's disease (PD) patients. 383 This study found no support for SV in PD patients, although these patients generally have reduced 5-HT activity and an increased risk of depression. These results may debilitate the model, although there may be several possible explanations for the negative finding.…”
Section: Limitations Of the Modelcontrasting
confidence: 54%
“…Depression and apathy in PD may be associated to different factors: depression is probably related to the dysfunction of different neurotransmitters, including dopamine, serotonin and norepinephrine [65][66][67][68][69][70][71], to the effects of dopaminergic therapies on other neurotransmitters [72] and to the amygdalar dysfunction [73][74][75] that affects patients since the early stages of PD and is considered an hallmark of depression [76]. Apathy is probably more related to the hypostimulation of OFC, an area involved in affective processing, which is affected in PD patients in moderate/advanced stages of the disease [49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…HA and PD could be caused by shared genetic and/or early environmental risk factors that predispose subjects, independently, to both PD and certain personality traits: therefore the presence of affective disorders in PD may be characterized as a part of a chronic maladaptive strategy belonging to an affective/ personality trait, rather than being state dependent [86][87][88][89]. Conversely, the increased HA could be state dependent and due to the presence of affective disorders; in this perspective many factors could contribute to the high tendency toward negative affect of PD patients, resulting in high rates of affective disorders and high HA: the deficit of serotonin [90][91][92] that characterizes this clinical population since the early clinical stages [93]; the early amygdala dysfunction of PD [94][95][96] which is considered a hallmark of depression and anxiety [97,98]; the executive dysfunction that characterizes PD patients from the early clinical stages [99] and that represents a risk factor for the development of depression in the elderly [100].…”
Section: High Harm Avoidancementioning
confidence: 99%